DEVELOPMENT OF ARTIFICIAL INTELLIGENCE BASED ANIMATION VIDEO LEARNING MEDIA ON OBJECT TRANSFORMATION FOR 4TH GRADE STUDENTS - Adelia, Karina Martha; Suratmi, Suratmi (JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
This research developed artificial intelligence (AI)-based animated video learning media for fourth-grade students at SD Negeri 157 Palembang to facilitate instruction on changes in the physical form of objects. The validity and practicality of the media were evaluated using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model for research and development. Media experts rated the media as highly valid (88%). Material experts assessed it as very valid (92%), and practitioner experts rated it as extremely valid (98%). Usability trials further supported these findings. Individual participants obtained a perfect score (100%), while large-group participants rated the media as very practical (96%). The effectiveness evaluation yielded an N-gain score of 0.75, categorized as high, and indicates substantial improvement in students’ cognitive learning outcomes from the pretest to the posttest. These results demonstrate that the animated video media enhances students’ comprehension, motivation, and engagement in science learning. With visually rich and accessible videos, measurable benefits emerged for elementary students. The product thus proves effective as a teaching tool and represents an innovative instructional approach in the classroom.